Lipid raft proteome reveals that oxidative phosphorylation system is associated with the plasma membrane. (December 2010) - Kim, Bong-Woo; Lee, Chang Seok; Yi, Jae-Sung; Lee, Joo-Hyung; Lee, Joong-Won; Choo, Hyo-Jung; Jung, Soon-Young; Kim, Min-Sik; Lee, Sang-Won; Lee, Myung-Shik; Yoon, Gyesoon; Ko, Young-Gyu
Although accumulating proteomic analyses have supported the fact that mitochondrial oxidative phosphorylation (OXPHOS) complexes are localized in lipid rafts, which mediate cell signaling, immune response and host–pathogen interactions, there has been no in-depth study of the physiological functions of lipid-raft OXPHOS complexes. Here, we show that many subunits of OXPHOS complexes were identified from the lipid rafts of human adipocytes, C2C12 myotubes, Jurkat cells and surface biotin-labeled Jurkat cells via shotgun proteomic analysis. We discuss the findings of OXPHOS complexes in lipid rafts, the role of the surface ATP synthase complex as a receptor for various ligands and extracellular superoxide generation by plasma membrane oxidative phosphorylation complexes.